2019
DOI: 10.32615/ps.2019.069
|View full text |Cite
|
Sign up to set email alerts
|

Discovering trends in photosynthesis using modern analytical tools:More than 100 reasons to use chlorophyll fluorescence

Abstract: In this review, using the network analysis, based on the bibliometric data, collected from Web of Science Core Collection database, we followed the development of chlorophyll fluorescence research (CFR) during 1947-2018. We confirmed dramatic increase in diversity of CFR from late 90-ties and vigorous development of this discipline in the last ten years. They are parallel to an increase in number of research areas and institutions involved and were triggered by the accumulation of knowledge and methodological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The Chl a fluorescence evaluation can provide the knowledge to estimate the photosynthetic performance and consequently the plant function (Baker 2008, Brestič and Živčák 2013, Brestič et al 2018, Baba et al 2019. In the present study, photosynthetic function was in accordance with the Fv/Fm response to wastewater irrigation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The Chl a fluorescence evaluation can provide the knowledge to estimate the photosynthetic performance and consequently the plant function (Baker 2008, Brestič and Živčák 2013, Brestič et al 2018, Baba et al 2019. In the present study, photosynthetic function was in accordance with the Fv/Fm response to wastewater irrigation.…”
Section: Discussionsupporting
confidence: 70%
“…The effect of wastewater irrigation on Fv/Fm, PIABS, and Chl content was significant, and to the best of our knowledge, there has been no similar study in which Chl fluorescence was measured in different genotypes of wastewater-irrigated crops (Misra et al 2001, Strasser et al 2004, Li et al 2006, Kalaji et al 2011, 2017bBrestič and Živčák 2013, Guo and Tan 2015, Brestič et al 2018, Hajihashemi et al 2018, Stirbet et al 2018, Baba et al 2019. As crops are frequently exposed to the environmental stresses, the reliable and efficient tools in screening of the stress at early stage of crop growth are required (Brestič and Živčák 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Many parameters could be calculated from obtained data and provide information about the PSII and PSI functionality. Photosynthetic activity measurements (especially Chl a fluorescence parameters) have been widely used to screen and reveal the effects of these environmental factors on photosynthetic behaviour of plants (e.g., Strasser et al 2010, Ceppi et al 2012, Oukarroum et al 2015, Dabrowski et al 2016, Wijewardana et al 2016, Çiçek et al 2018, Kalaji et al 2018, Baba et al 2019. It has been reported that UV-B leads to downregulation of photosynthesis of Arabidopsis thaliana (Coffey and Jansen 2019, Khudyakova et al 2019, Schultze and Bilger 2019, blueberry (González-Villagra et al 2020), grapevine (Doupis et al 2016), sugar beet (Rahimzadeh Karvansara and Razavi 2019), and soybean (Choudhary and Agrawal 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the tools for assessing the dynamic changes occurring in the photosystems is chlorophyll fluorescence [18,19]. Emphasis on research on chlorophyll fluorescence and photosynthesis has increased the last decades, indicated by the steep increase from 1990 onwards of the number of publications relating to the keywords aforementioned [20].…”
Section: Introductionmentioning
confidence: 99%